Creation of skyrmions in van der Waals ferromagnet Fe3GeTe2 on (Co/Pd)(n) superlattice - Yang, M.; Li, Q.; Chopdekar, R., V; Dhall, R.; Turner, J.; Carlstrom, J. D.; Ophus, C.; Klewe, C.; Shafer, P.; NDiaye, A. T.; Choi, J. W.; Chen, G.; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2020)
Magnetic skyrmions are topological spin textures, which usually exist in noncentrosymmetric materials where the crystal inversion symmetry breaking generates the so-called Dzyaloshinskii-Moriya interaction. This requirement unfortunately excludes many important magnetic material classes, including the recently found two-dimensional van der Waals (vdW) magnetic materials, which offer unprecedented opportunities for spintronic technology. Using photoemission electron microscopy and Lorentz transmission electron microscopy, we investigated and stabilized Neel-type magnetic skyrmion in vdW ferromagnetic Fe3GeTe2 on top of (Co/Pd)(n) in which the Fe3GeTe2 has a centrosymmetric crystal structure. We demonstrate that the magnetic coupling between the Fe3GeTe2 and the (Co/Pd)(n) could create skyrmions in Fe3GeTe2 without the need of an external magnetic field. Our results open exciting opportunities in spintronic research and the engineering of topologically protected nanoscale features by expanding the group of skyrmion host materials to include these previously unknown vdW magnets.
Keywords: MULTILAYERS; LATTICE